Cretaceous bryozoan fossils from Needs Camp, South Africa - Duma, Nothando (Department of Biological Sciences, 2024)
Fossil Bryozoa in South Africa is understudied and has received little attention, despite the country's very rich geological and fossil heritage conservation. Published literature regarding bryozoan fossils from South Africa comprise of four papers with the most recent being a little over two decades old. The upper and lower Needs Camp quarries in the Igoda Formation, situated about 20 km northwest of East London, is of great scientific importance, necessitating that the sites be preserved for the purposes of research. The Needs Camp fossils include corals, foraminifera, bivalves etc. and date the deposits to the Late Cretaceous. Gaps in the fossil record hamper efforts to understand important geological events and palaeoenvironmental conditions. This study aims to examine and identify some bryozoans from the Needs Camp fossil deposits lodged in the marine invertebrate collections of the Iziko South African Museum, Cape Town. The approach will be a combination of traditional morphological methods and cutting-edge scanning electron microscopy (SEM) technology. Limestones were dissolved by water, the fragments and fossils extracted from the stone were sieved and placed in an ultrasonic bath. These were left to dry then later examined under a light microscope, after they were separated into broad categories according to their colony form and examined using the SEM. In total, 14 species were identified from this study, of which ten were identified to genus-level. Genera reported for the first time in South Africa from this study, include Supercytis, Onychocella, Aechmella, Ogiva, Gastropella, Chiplonkarina, Pithodella, Wilbertopora, Hoplocheilina, Tremogasterina and Bountyella. Keywords: Bryozoa, fossils, Needs Camp, Late Cretaceous, scanning electron microscopy